Dampak Pembuangan dan Pembakaran Sampah Terhadap Lingkungan di Gunung Salam - Rieke Nur Salsabilatul Khusna; Unaisa Rahma Febriani; Rina Rahayu (ECOTAS, 2024)
Mount Salam is located in Salamkanci Village. Natural beauty makes the mountains often passed by humans. Unfortunately, the behavior of throwing garbage by humans results in pollution of the ecosystem on Mount Salam. This research was conducted to identify the types of garbage in Mount Salam and analyze the impact that will be caused. This research uses research journals as references. The research method is a combination of literature review and qualitative research. The results of the study explained that Mount Salam was once a natural tourist spot that had experienced forest fires. The trigger of this forest fire is because people don’t heed warning writings and litter. Land that isn’t so large causes garbage to accumulate. The fire occurred due to human activities who were smoking and throwing cigarette butts towards the land with a lot of garbage. Another trigger is due to friction between dry branches around land full of garbage to cause sparks. The fires provide pollution and adverse impacts, especially in the health sector. Therefore, the Regional Government must be firm in steps to maintain the cleanliness of the environment by implementing clear regulations, giving instructions to the community not to carry out littering.